Augmented Reality Implementation in Laptop Product Promotion Media Using Web-Based QR-Codes - Dini Destiani Siti Fatimah; Ayu Latifah; Albie Firgi Bahari (Journal of Electrical, Electronic, Information, and Communication Technology, 2024)
Technological developments were created for various needs, such as science, especially in the information field. This development has a very positive impact on technology users who promote electronic-based products. Augmented Reality is a tool to promote various products, especially to find out the specifications of electronic devices such as laptops, where users can view additional information relevant to the product being promoted via mobile devices such as smartphones or tablets. QR codes can also direct users to promotional websites that contain complete information about the laptop products being promoted. This research uses the MDLC (Multimedia Development Life Cycle) methodology to ensure that the built system can meet user needs and ensure effective use of AR and QR-code technology in laptop product promotion. The research stages consist of concept, design, material collecting, assembly, testing, and distribution. The results of the study show that the use of Augmented Reality as a promotional support medium is able to create innovative experiences for users, resulting in increased effectiveness in product promotion. By applying the Blackbox approach in testing application functions, the results show that all application components run according to predetermined expectations. The application of Augmented Reality technology in this application was carried out according to plan, successfully displaying product objects in 3D through the implementation of Augmented Reality.